Beyond the photocycle — how cryptochromes regulate photoresponses in plants?. (October 2018) - Wang, Qin; Zuo, Zecheng; Wang, Xu; Liu, Qing; Gu, Lianfeng; Oka, Yoshito; Lin, Chentao
Abstract : Cryptochromes (CRYs) are blue light receptors that mediate light regulation of plant growth and development. Land plants possess various numbers of cryptochromes, CRY1 and CRY2, which serve overlapping and partially redundant functions in different plant species. Cryptochromes exist as physiologically inactive monomers in darkness; photoexcited cryptochromes undergo homodimerization to increase their affinity to the CRY-signaling proteins, such as CIBs (CRY2-interacting bHLH), PIFs (Phytochrome-Interacting Factors), AUX/IAA (Auxin/INDOLE-3-ACETIC ACID), and the COP1-SPAs (Constitutive Photomorphogenesis 1-Suppressors of Phytochrome A) complexes. These light-dependent protein–protein interactions alter the activity of the CRY-signaling proteins to change gene expression and developmental programs in response to light. In the meantime, photoexcitation also changes the affinity of cryptochromes to the CRY-regulatory proteins, such as BICs (Blue-light Inhibitors of CRYs) and PPKs (Photoregulatory Protein Kinases), to modulate the activity, modification, or abundance of cryptochromes and photosensitivity of plants in response to the changing light environment.